The Addition of Spiritual Dimension on Customer Value to Investigate the Relationship of Customer Value, Customer Satisfaction and Behavior Intention on Islamic Banks Saving Products in Indonesia - Afiff, Adi Zakaria; Astuti, Rifelly Dewi (UI Scholars Hub, 2021)
This study propose the addition of a spiritual dimension in the formation of customer value, in addition to the functional, social and emotional dimension of customer value that has already been empirically tested in previous studies, among customers who own saving products at Islamic banks in Indonesia. The study also investigate the relationship between customer value and customer satisfaction, and the relationship between customer satisfaction and customer behavioral intentions among these Islamic banks customers. The results show that spiritual dimension is significantly related to the customer value together with all three other dimensions (functional, social and emotional) of customer value. All dimensions have significant relationship with customer value. Finally the results also show that customer value positively influence customer satisfaction, and customer satisfaction positively influence customer behavior intentions.